Phrenic palsy and analgesic quality of continuous supraclavicular vs. interscalene plexus blocks after shoulder surgery. Issue 8 (20th April 2016) - Wiesmann, T.; Feldmann, C.; Müller, H. H.; Nentwig, L.; Beermann, A.; El‐Zayat, B. F.; Zoremba, M.; Wulf, H.; Steinfeldt, T.
Abstract : Background: Hemidiaphragmatic palsy is a common consequence of the interscalene brachial plexus block. It occurs less commonly with the supraclavicular approach. Register data suggest that the analgesic quality of a supraclavicular blockade is sufficient for arthroscopic shoulder surgery, although data on the post‐operative analgesic effect are lacking. Methods: After approval by the ethics committee, patients having arthroscopic shoulder surgery under general anaesthesia were randomized to receive a continuous interscalene or supraclavicular blockade. Phrenic nerve function was evaluated through ultrasound examination of the diaphragm in combination with spirometry. Pain scores at rest and activity etc. were determined before catheter insertion, during observation in the post‐ anaesthesia care unit (PACU) and on post‐operative day 1 (POD1). The initial application of 10 ml of ropivacaine 0.2% was followed by continuous application of 4 ml of ropivacaine 0.2%, plus a patient controlled analgesia (PCA) bolus of 4 ml/h. Results: One hundred and twenty patients were randomized, of which 114 data sets were analysed. Complete hemidiaphragmatic paresis occurred in 43% of the interscalene group vs. 24% in the supraclavicular group during PACU stay. Rates of dyspnoea and hoarseness were similar. Horner's syndrome occurred in 21% of the interscalene but only 3% of the supraclavicular group on POD1. Pain scores were comparable for pain at rest and during stress at each time point. Conclusions: This trial showed a significantly greater incidence of phrenic nerve palsy of the interscalene group in PACU, but not on POD1. Post‐operative analgesic quality was similar in both groups. Continuous supraclavicular blockade is a suitable alternative to the continuous interscalene technique.